Analisis Supply Chain Risk ManagementProduk Susu Sapi Segar dengan Pendekatan Analytical Network Process (ANP ) di Koperasi Peternak Bandung Selatan, Pangalengan - , LANGKAH TAWANG P ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The condition of milk nowadays was not only on the Pangalengan but Indonesia is facing various global challenges and problems including many risks that involved in the milk supply chain as well as from quality and quantity point of view that may affects the milk product from producer until the consumers. This study aims at indentifying and risk processing that may occur in every fresh milk supply chain. The risk that was indentifying then became the priority that will be solved using ANP. This study was done using deep interview in the Pangalengan area using convenience sampling to the subject in every tiers supply chain. Risk identification and anticipation that occurs in the supply chain activity needs a good risk management in the supply chain. Risk processing analyze was based on the risk assessment standard from ISO 31000:2009 which then the identified risk became the problem priority using analytical network process (ANP). The result from this study shows that there were 5 cluster risks that consist from 9 criteria. Based on the result of ANP, result of the fixed risk priority sequence were the need of livestock cost was still high (0.149), incapable of producing consistent quality (0.143), low shelf life (0.130), low fresh milk productivity (0.123), unqualified product with the standard (0.117), untimed milking (0.104), low milk price (0.085), inconsistent of the milk quantity (0.076), and far location of fresh milk collecting (0.073). The priority of this management was done using alternative solution and comparing from risk value from the mapping risk to preface which risk needs to be manage first.